DRUG-INDUCED HYPERSENSITIVITY SYNDROME (DRESS-SYNDROME) IN MONOZYGOTIC TWINS. A CASE FROM PRACTICE - Ishkova, Natalya Semenovna; Pisareva, Maria Vladimirovna; Kaznacheev, Konstantin Sergeevich; Gerashchenko, Natalia Viktorovna; Kaznacheeva, Larisa Fedorovna; Molokova, Anzhelika Valerievna (Mother and Baby in Kuzbass, 2026)
Drug-induced hypersensitivity syndrome (drug rush with eosinophilia and systemic symptoms; DRESS-syndrome) is a variant of an allergic reaction with systemic manifestations and eosinophilia. DRESS-syndrome is a rare disease that occurs with a frequency of 1 : 1000 to 1 : 10000, but is characterized by a high mortality rate of up to 10%.The article presents data from clinical observation of the course of an allergic reaction against the background of carbamazepine drug therapy in two identical male twin patients. The symptoms of DRESS-syndrome included diffuse skin rashes, febrile fever, enlarged lymph nodes, hypereosinophilia in the blood, hepatomegaly, and cytolysis syndrome. It is noted not only the similarity of the list of clinical manifestations of an adverse reaction, but also the synchronicity of their development.Pathogenetic therapy led to a complete regression of skin syndrome, lymphadenopathy, fever, and cytolysis syndrome. The children were discharged in satisfactory condition on the 25th day from the moment of hospitalization.
Keywords: DRESS-syndrome; drug allergy; carbamazepine; monozygotic twins